A Study on Sample Size Determination in Survey Research - Anokye M. Adam (New Ideas Concerning Science and Technology Vol. 4, 2021)
Obtaining a representative sample size remains critical to survey researchers because of its implication for cost, time and precision of the sample estimate. However, the difficulty of obtaining a good estimate of population variance coupled with insufficient skills in sampling theory impede the researchers’ ability to obtain an optimum sample in survey research. One of the key challenges that social science researchers face in survey research is the determination of appropriate sample size which is representative of the population under study. This is to ensure that findings generalized from the sample drawn back to the population are with limits of random error. This paper proposes an adjustment to the margin of error in Yamane’s (1967) formula to make it applicable for use in determining optimum sample size for both continuous and categorical variables at all levels of confidence. A minimum sample size determination table is developed for use by researchers based on the adjusted formula developed in this paper.